2022
DOI: 10.1371/journal.pcbi.1010281
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing superspreading potential of infectious disease: Decomposition of individual transmissibility

Abstract: In the context of infectious disease transmission, high heterogeneity in individual infectiousness indicates that a few index cases can generate large numbers of secondary cases, a phenomenon commonly known as superspreading. The potential of disease superspreading can be characterized by describing the distribution of secondary cases (of each seed case) as a negative binomial (NB) distribution with the dispersion parameter, k. Based on the feature of NB distribution, there must be a proportion of individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
0
3
2
Order By: Relevance
“…SAI incidence was 15.8% among household contacts, which was not consistent with the incidence of SAI in Denmark in a published study (21). This may be because the local government in Shenzhen immediately compulsorily isolated household contacts at designated facilities after the index cases were diagnosed, resulting in a relatively low secondary attack rate compared with published study in Denmark (21). In addition, we observed that individuals who received booster vaccination had a lower risk of SAI compared with unvaccinated or only partial vaccinated subjects although the effectiveness was not very high.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…SAI incidence was 15.8% among household contacts, which was not consistent with the incidence of SAI in Denmark in a published study (21). This may be because the local government in Shenzhen immediately compulsorily isolated household contacts at designated facilities after the index cases were diagnosed, resulting in a relatively low secondary attack rate compared with published study in Denmark (21). In addition, we observed that individuals who received booster vaccination had a lower risk of SAI compared with unvaccinated or only partial vaccinated subjects although the effectiveness was not very high.…”
Section: Discussioncontrasting
confidence: 89%
“…Moreover, household contacts had a higher SAI risk than non-household contacts. SAI incidence was 15.8% among household contacts, which was not consistent with the incidence of SAI in Denmark in a published study ( 21 ). This may be because the local government in Shenzhen immediately compulsorily isolated household contacts at designated facilities after the index cases were diagnosed, resulting in a relatively low secondary attack rate compared with published study in Denmark ( 21 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Individuals with infections who were associated with zero secondary infections and the close contacts of these individuals were excluded from estimating the secondary attack rate. We also considered the individual reproduction number, defined as the expected number of infections spread by 1 individual with an infection, by calculating the mean number of secondary infections associated with primary infections . The proportion of supercritical transmission is defined by the ratio at which the individual reproduction number is greater than 1, and this was measured by the proportion of individuals who spread infections who were associated with more than 1 offspring infection.…”
Section: Methodsmentioning
confidence: 99%
“…Following this, the negative binomial model has been widely adopted as the canonical model for analyzing heterogeneous transmission data, although several alternatives have been proposed (e.g., see Refs. 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%